Paralisia cerebral: repercussões no contexto familiar - Sandor, Elizane Regina Santos (2011)
Cerebral Palsy (CP) is a chronic condition that affects the motor development and posture of the child, often accompanied by disorders in speech, hearing, cognition, sensory perception, among others. This situation is responsible for changes and limitations in daily activities of children requiring adaptations by the family that plays a fundamental role in the rehabilitation process of children with CP, and partner and co-responsibility in child care. This study aims to evaluate the experience of families of children with CP treated at an outpatient child and investigate the impact of chronic disease in children in the family context. This is a qualitative study, which adopted the theoretical Symbolic Interactionism (SI). The study site was a specialized unit in the care of children in a midsize city in the interior of São Paulo state. To collect data we used an instrument composed of two parts: the first part consisted in gathering information related to family composition and sociodemographic conditions of the members, the second part featured questions relating to the experience of family in the PC in the family context. The interviews with family members were recorded and transcribed. The content analysis and thematic Bardin, was the technique adopted for data analysis. We apprehend this study that the PC has a significant effect on the family and among those experiences, which leaves the family more un easy is the lack of support emotional/instrumental from professionals and social networking. The study also identifies the urgent need of nursing care to be part of the family of the child with CP in order to add knowledge to the multidisciplinary team and care paid to redeem the family unit.